If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -11x = 61 Solving 6 + -11x = 61 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -11x = 61 + -6 Combine like terms: 6 + -6 = 0 0 + -11x = 61 + -6 -11x = 61 + -6 Combine like terms: 61 + -6 = 55 -11x = 55 Divide each side by '-11'. x = -5 Simplifying x = -5
| 3m+2p=8 | | g/g+12=16 | | 4x-4(5x-14)=184 | | -8x+10=42 | | y=[x] | | Y=-6+8 | | 2x+5-5x=16 | | 7x+4(-6x-11)=143 | | 4k-6+4k=10 | | 2x+7-3=10 | | 4(3-5)=4x | | -5n=15 | | 2x+11=3x-11 | | x/5=-5 | | 6x+6x-2=34 | | -3x-2+15x=58 | | 3(2x-9)+4x=2(4x-3)-3 | | x^2+5x-185=0 | | 3r-2+2r=23 | | 6x-3=18x+1 | | x=12+0.25x | | (-3m+5)+(m-11)= | | -2b=0 | | 5x-15=x-5 | | 4(2x+1)=27+3x(2x-5) | | p/3=-4 | | y/2-2y/3-2/6=y+2/6 | | 5p+14=8p+4 | | r/5=4 | | 7+c=-10 | | 5x+12+81=0 | | 2y+2x=7y |